Incidence and Significance of Hypermetabolic PET-CT Findings in Unilateral TVF Motion Impairment. (November 2019) - Stanisce, Luke; Renzi, Timothy; Paripati, Nikita; Ahmad, Nadir; Spalla, Thomas C.; Roth, Howard L.; Koshkareva, Yekaterina
Objective: To determine the incidence and significance of asymmetric hypermetabolic laryngeal findings on positron emission tomography–computed tomography (PET-CT) in patients with unilateral true vocal fold (TVF) motion abnormalities. Study Design: Retrospective cohort. Setting: Single-center tertiary care institution. Subjects and Methods: The medical records of patients with unilateral TVF motion abnormalities were reviewed. The incidence of normal and asymmetric hypermetabolic laryngeal findings was calculated in patients who underwent PET-CT and laryngeal examination, operative laryngoscopy with biopsy, or injection medialization laryngoplasty. Results: A total of 135 patients with unilateral TVF motion abnormalities underwent PET-CT. After exclusion of patients who completed new or surveillance imaging for a laryngeal neoplasm (n = 27), asymmetric hypermetabolic findings in the larynx were noted in 21 (19%) cases: 13 (12%) on the contralateral side of the impaired TVF, 8 (7%) on the ipsilateral side. Two (25%) patients with ipsilateral hypermetabolism had concerning subsequent fiberoptic laryngeal examinations prompting operative biopsy. There was no evidence of inflammatory or neoplastic disease in all patients with contralateral hypermetabolic findings. Fifteen patients completed PET-CT scans after injection medialization procedures; 6 (40%) displayed avidity ipsilateral to the side of the injection. The median time from injection to scan was 27 days, as opposed to 193 days in the unremarkable scans ( P = .011). Conclusion: Contralateral hypermetabolism in patients with unilateral TVF motion abnormalities may represent a false-positive finding. Ipsilateral hypermetabolic uptake without recent fold instrumentation warrants prompt diagnostic evaluation.